Promoting resilience among medical students using the Wadi framework: a clinical teacher’s perspective - Shorbagi, Ali Ibrahim (Frontiers in Medicine, 2024)
Resilience is essential for medical students to navigate the challenges of their education and future careers. Defined as the ability to adapt well in the face of adversity, resilience can be learned and is critical for maintaining mental health. Medical educators play a pivotal role in fostering resilience by integrating it into both formal and informal curricula, including the hidden curriculum, which can significantly influence students' coping strategies. Research highlights the importance of resilience training in reducing depression and anxiety among students, underscoring its necessity as a core component of medical education. This essay presents the Systematic Assessment for Resilience (SAR) framework, which provides a comprehensive approach to promoting resilience through four key constructs: self-control, management, engagement, and growth. Practical strategies for each construct are discussed, including assessment mapping, time management, and the use of formative assessments to enhance students' preparedness and self-control. Engagement is fostered through collaborative assessments, open book exams, and regular formative feedback, while growth is encouraged via self-reflection and faculty development.Implementing the SAR framework has shown positive outcomes, with students reporting reduced anxiety and improved performance. However, further exploration and institutional support are needed to fully integrate these strategies into medical education. The SAR framework offers a feasible and effective method for cultivating resilience, contributing to students' mental well-being and equipping them to face future challenges in their medical careers. Continued refinement and broader institutional adoption will be crucial to sustaining the impact of resilience training in medical education.